2004
DOI: 10.1029/2003jd004270
|View full text |Cite
|
Sign up to set email alerts
|

A study of long‐term trends in mineral dust aerosol distributions in Asia using a general circulation model

Abstract: Dust events have been observed in Japan with high frequency since 2000. On the other hand, the frequency of dust storms is said to have decreased in the desert regions of China since about the middle of the 1970s. This study simulates dust storms and transportation of mineral dust aerosols in the east Asia region from 1981 to 2001 using an aerosol transport model, Spectral Radiation‐Transport Model for Aerosol Species (SPRINTARS), implemented in the Center for Climate System Research/National Institute for Env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
(23 reference statements)
3
22
0
Order By: Relevance
“…As shown in Fig. 13, the dust source region in Mukai et al (2004) is in good agreement with the region identified as having large ω 0 values in our study. This region also corresponds to the Takla Makan and Gobi deserts on geological maps.…”
Section: Comparison Of Dust's Optical Properties Between Thesupporting
confidence: 89%
See 4 more Smart Citations
“…As shown in Fig. 13, the dust source region in Mukai et al (2004) is in good agreement with the region identified as having large ω 0 values in our study. This region also corresponds to the Takla Makan and Gobi deserts on geological maps.…”
Section: Comparison Of Dust's Optical Properties Between Thesupporting
confidence: 89%
“…13 (Herman et al, 1997). Mukai et al (2004) also estimated that carbonaceous and dust aerosols were transported around the region with the blue box in Fig. 13.…”
Section: Comparison Of Dust's Optical Properties Between Thementioning
confidence: 98%
See 3 more Smart Citations